Methodology of Teaching the Russian Language - Nuriddinovna, Mardieva Dilrabo (Research Parks Publishing LLC, 2022)
Russian language, as already recognized by all, should serve as the main vehicle of education. Here, by education, of course, we mean not the accumulation of all kinds of knowledge in the head, but that spiritual development in which the word becomes deed and both serve as an expression of the deepest moral convictions in a person. Is it possible, however, to somewhat limit the difficult task that is assigned to the teacher of the native language? Could it not be more precise to determine the limits within which he can usefully operate here to express a few of my opinions concerning the very method of teaching: these opinions, of course, are not new in many respects, and could be expressed more fully by teachers who are more experienced than I am; but with our common desire to explain to ourselves as clearly as possible the purpose and scope of each science that serves the development of youth, it is our duty to express those convictions that come from a sincere desire for good.